Genome-wide association study of lipidomes of Arabidopsis thaliana accessions identifies genes affecting lipid metabolism under unstressed and stressed conditions - Song, Yu (Kansas State University, 2022)
In unfavorable conditions, plants make adjustments of metabolic pathways to adapt to the environment. As essential components of plant cells, lipids respond to environmental stresses in a variety of ways, including maintaining membrane structure and signaling. The model plant Arabidopsis thaliana is widely distributed in Eurasia and its natural accessions have tremendous genetic and phenotypic diversity, which enables genome-wide association study (GWAS) to identify candidate genes affecting lipid metabolism under stressed and unstressed conditions. A lipidomics approach was established, allowing quantitative analysis of 358 lipid analytes in Arabidopsis leaf tissues. The lipidomics approach was applied to Arabidopsis accession Columbia-0 (Col-0) to investigate lipid changes in leaf tissues under cold and mechanical-wounding stresses. In cold, the most prominent variation in leaf tissue of Col-0 was the large accumulation of triacylglycerols (TAGs) and major phospholipids containing very long chain fatty acids (VLCFAs). The highly unsaturated 54C-TAG species showed large induction after -2 °C treatment, while the less unsaturated 50C- and 52C-TAGs accumulated during cold acclimation and declined at -2 °C. Mechanical wounding treatment resulted in large variations in the leaf lipid profile with the greatest change being the accumulation of lipids with oxidized fatty acyl chains. Application of the lipidomics approach to natural accessions of Arabidopsis grown under unstressed condition or subjected to cold or mechanical wounding showed that large variations exist in Arabidopsis leaf lipidomes. Among the candidate genes identified from GWAS under cold stress are genes, including FAD2, FAD7, LOH2, KCS9, and FAB1, known to be involved in fatty acyl desaturation, fatty acyl elongation, and sphingolipid synthesis. A strong correlation between certain components of the cold-induced lipidome and freezing tolerance was observed in the investigated Arabidopsis accessions, suggesting potential roles for specific lipids and associated genes in plant freezing tolerance. Two genomic regions, found only under wounding stress, are strongly associated with large numbers of esterified oxophytodienoic acid (OPDA) and esterified dinor-oxophytodienoic acid (dnOPDA) lipids, as well as with free OPDA. One of these regions contains three genes, AT3G25760 (AOC1), AT3G25770 (AOC2), and AT3G25780 (AOC3), while the other region contains one gene, AT4G15440 (HPL1). Haplotype analysis of gene expression level demonstrated that a SNP, associated with oxidized lipid level, in the upstream region of HPL1 is also associated with expression of HPL1 upon wounding. Additional lipidomic analysis on T-DNA insertion and overexpression mutants suggested that AOC1, AOC2, and AOC3 all play positive effects on production of esterified OPDA and dnOPDA lipids in Arabidopsis leaves under wounding stress. This work utilizes GWAS to analyze and interpret complex lipidomics data in Arabidopsis, leading to advances in understanding plant lipid metabolism and stress responses. The list of candidate genes related to lipid metabolism during plant stress responses provides a resource for future engineering of plants with altered levels of lipids that improve stress tolerance.
Keywords: Lipidomics; Genome-wide association study; Arabidopsis; Cold; Wounding